How natural disasters and environmental fears shape American climate attitudes across political orientation - Christopher R. H. Garneau; Heather Bedle; Rory Stanfield (npj Climate Action)
Abstract Climate change remains a polarizing issue in the United States, with conservatives expressing greater skepticism regarding its risks. We investigate how fear shapes climate attitudes across political orientations. Utilizing data from a 2023 online survey, results support hypotheses that conservatives demonstrate lower climate concern and that fear of natural and environmental disasters increases climate concern. Interaction results show that fear of anthropogenic environmental disasters elicits greater climate concern amongst conservatives. At high levels of ecological fear, the political divisions diminish as all orientations converge on higher levels of acknowledging climate risks and causes. Practically, this relationship highlights messaging opportunities by focusing on relevant environmental threats that aid in influencing conservatives to build collective support across political divides. Theoretically, these findings challenge expectations of dominant paradigms related to threat perception and political orientation, contributing to the ongoing development of new models that more thoroughly represent the relationship between these multifaceted constructs.